Electrodermal Activity - Boucsein, Wolfram; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2012)
Electrodermal Activity, Second Edition Wolfram Boucsein From EEG technology to the polygraph, psychophysiology has become part of mainstream science, encompassing a number of subspecialties. In particular, the study of electrodermal activity (EDA)—the activation of sweat glands in the skin in response to stress or other stimuli—has given psychologists many useful applications over a variety of settings. Increased scholarly interest in EDA has brought with it a wealth of improvements in recording, analyzing, and applying data—and a need to make this knowledge available in a readable, practice-oriented format. The Second Edition of Electrodermal Activity brings together research from biology, psychology, and physics for a comprehensive understanding of the subject and its potential across mental health and medical disciplines. As in the original volume, the reader is given a thorough grounding in electrodermal phenomena: the anatomy and physiology of the electrodermal system, the biophysics of measurement, and the history of the field. From there, the book incorporates two decades’ worth of new knowledge, not just on innovative measurement and analytic techniques but also in the area of applications, with new or completely rewritten chapters on the use of EDA in: Decision-making. Human-computer interaction. Neurological diseases and brain lesions. Anxiety, depression, psychopathy, and schizophrenia. Detection of deception. Biofeedback, product evaluation, and more. Retaining the breadth and depth of information that made the original a bedrock text, this Second Edition of Electrodermal Activity is imminently useful to clinical psychologists, psychophysiologists, and forensic psychologists alike.
Keywords: Clinical psychology; Psychology; Personality; Social psychology; Clinical Psychology; Law and Psychology; Personality and Social Psychology